Use of Evidence to Inform Agricultural Policy Decisions : What have We Learned from Experience in Africa? - Delgado, Christopher; Brooks, Karen; Derlagen, Christian; Haggblade, Steven; Lawyer, Kate (World Bank, Washington, DC, 2020)
Agricultural policymakers in Africa increasingly face the need for policy options based on evidence-based analysis to promote agricultural transformation and to adapt to climate change. Furthermore, data and analytical tools to support informed agricultural policymaking are increasingly abundant thanks to investment in these areas, mostly from external sources. Still, the use of hard data and robust analyses linked to outcomes are still rare in most agricultural policymaking in the region. Today, ministries of agriculture (MoAs) are increasingly under pressure to show ministries of economy and finance (MoEFs) both the rationale behind spending and the impact of past spending, particularly net estimated impacts on forex and fiscal balances. Even so, at present most African governments are still under-spending on agricultural public goods such as research, extension, and infrastructure. The present paper focuses on what can be learned to improve outcomes from experiences promoting the increased use of evidence in agricultural policymaking.